Detection of Polystyrene Microplastic Particles in Water Using Surface-Functionalized Terahertz Microfluidic Metamaterials - Park, Sae June; Ahn, Yeong Hwan (Applied Sciences (Switzerland), 2022)
We propose a novel method for detecting microplastic particles in water using terahertz metamaterials. Fluidic channels are employed to flow the water, containing polystyrene spheres, on the surface of the metamaterials. Polystyrene spheres are captured only near the gap structure of the metamaterials as the gap areas are functionalized. The resonant frequency of terahertz metamaterials increased while we circulated the microplastic solution, as polystyrene spheres in the solution are attached to the metamaterial gap areas, which saturates at a specific frequency as the gap areas are filled by the polystyrene spheres. Experimental results were revisited and supported by finite-difference time-domain simulations. We investigated how this method can be used for the detection of microplastics with various solution densities. The saturation time of the resonant frequency shift was found to decrease, while the saturated resonant frequency shift increased as the solution density increased.
Keywords: lab-on-a-chip; metamaterials; microplastics; sensors; terahertz spectroscopy